Development of an ex Vivo Ileal Explant Culture Method for Amplified Production and Differential Measurement of Nitrite - Kallapura, G.K.; Hernandez-Velasco, X.; Piekarski, A.; Lassiter, K.; Pumford, N.R.; Tellez , G.; Bottje, W.G.; Hargis, B.M.; Faulkner, O.B. (International Journal of Poultry Science, 2015)
Quantifying nitrite, a metabolite of nitric oxide (NO), is a well-established marker for the production of reactive oxygen species and an indirect measurement for inflammation. Under optimal culture conditions various cell based systems, like peripheral blood mononuclear cells, abdominal macrophages along with many macrophage based cell lines, would produce measurable nitrite by 24 to 72 h post stimulation with an agonist. We have developed a rapid ex vivo ileal explant culture method that can measure elevated nitrite within 3 h of lipopolysaccharide (LPS) stimulation in vitro. The model was developed to measure elevated NO along with the ability to measure differential NO among control and treated groups, with an aptitude to screen potential anti-inflammatory and anti-oxidant candidates. Ileal cross-sections (0.5 cm2) were cultured from chickens that were challenged for three consecutive d with Salmonella Enteritidis in the drinking water. Quantification of NO in these inflamed ileal explants provided a suitable screening model which potentially mimics in vivo intestinal conditions. This model could rapidly detect NO, at a greater magnitude than other cell culture methods. The ileal explants produced elevated nitrite by 3 h with a maximal magnitude of 478.42 μM nitrite 6 h post LPS stimulation. The model was also successful in measuring differential NO between the control and groups treated with potential anti-inflammatory compounds. This unique and simple ileal explant culture method provides a rapid screening system for inflammation modulation and the potential to quantify other inflammatory markers that are indicative of other gut pathogens to evaluate candidates for regulating inflammation.